RANCANG BANGUN WEBSITE E-LEARNING SEKOLAH DASAR NEGERI TAHAWA 1 MENGGUNAKAN PHP DAN MYSQL - Felicia Sylviana; Enny Dwi Oktaviyani; Yudianto Setiawidodo (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
SDN Tahawa 1 is one the Elementary School in Central Kahayan District. As an Education Institute, SDN Tahawa 1 has Very Important role in knowledge Science Development to improve the Education quality which is being held . To achieve the purpose explaining above, it is need an adequate infrastructure and equipment to maximize Teaching learning process at SDN Tahawa 1. One of the infrastructure using Technology that can maximize Progress in teaching and learning process is an e-learning website.This website is created using PHP , MySQL database and application development methods UWE ( UML-Based Website Engineering ) program through several stages of analysis. These Stages are requirements model, content model, navigation model, and presentation model. Blackbox test results showed that the e-learning website State Primary School Tahawa 1 can manage features such as e-learning materials, assignments and quizzes. This feature becomes media electronic learning (e-learning) that can help teachers deliver lessons online that can be accessed anytime and anywhere using the Internet. Besides this the website also can manage features school profiles which gives an overview of information to the public about the state elementary school Tahawa 1.